Effect of hot air gradient drying on quality and appearance of beef jerky. (October 2021) - Shi, Shuo; Zhao, Mengna; Li, Ying; Kong, Baohua; Liu, Qian; Sun, Fangda; Yu, Weihua; Xia, Xiufang
Abstract: The quality and appearance of beef jerky during hot air gradient drying were investigated. The temperatures were sequentially increased from 40 °C to 50 °C–60 °C, and the corresponding drying times were 0.5 h–1 h - 2.5 h, 0.5 h–2 h - 1.5 h, 1 h–1 h - 2 h and 1 h–2 h - 1 h in 4 groups. With increasing drying temperature and time, the shear force, yellowness ( b *) and metmyoglobin of the samples increased, and moisture content (MC), lightness ( L *), redness ( a *), oxymyoglobin and heme content of the samples decreased. After drying at 60 °C, the lower MC, shear force, b * and metmyoglobin content and the higher L *, a *, oxymyoglobin and heme content of the samples that were dried in the group 4 (40 °C −1 h, 50 °C −2 h and 60 °C −1 h) process were observed. In combination with the visual appearance, the samples that were dried in the group 4 process exhibited enhanced quality and appearance. Highlights: Formation mechanism of beef jerky quality and appearance was revealed. Correlation between beef jerky drying conditions and quality was established. Quality and appearance of jerky under 40 °C-1 h, 50 °C-2 h and 60 °C-1 h was excellent.